The Radical Phase of the Oxford Movement - Griffin, John R. (The journal of ecclesiastical history, 1976)
Hitherto we have depended on the State, i.e. on the ruling powers in the country—the King and the aristocracy … But these recollec-tions of the past must not engross our minds, or hinder us in looking at things as they are, and as they will be soon, and inquiring what is intended by Providence to take the place of the time-honoured instrument which he has broken (if it is yet to be broken) the regal and aristocratic power, I shall disgust many men when I say, we must look to the people’. (J. H. Newman, British Magazine, 1833).